PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) DALAM PEMBELAJARAN IPS DENGAN MEDIA VISUALISASI MUSEUM GULA GONDANG WINANGUN UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VIII H SMP NEGERI 1 SURAKARTA TAHUN 2013/2014 - Supanti, S.; Joebagio, Hermanu; Musadad, Akhmad Arif (HISTORIKA, 2017)
Research class action aims to understand how the model the problem based learning (PBL) in learning social science by visualization Gula Gondang Winangun museum to improve critical thinking in Junior High School 1 Surakarta grade VII 2013/2014. The method of this research is a descriptive qualitative research results from the class in the form of treatment with the subject of the research is grade VIII H totalling 26 students, comprising 10 men and 16 women. Research data obtained from the observation of learning activities, the informant, documents and photographs of the value of the activities. Minimal standards pass social science class VII 8,0 with Minimal standards klasikal 85%. After treatment for 3 cycle increased results achieved is the value of tests the ability of think critically in cycle I: 63.38 %, cycles II: 80.76 % and cycle III: 92.30 % worth average cycle I: 76.92 , cycles III: 80.72 and cycle III: 85.0.The value of the capacity to critical thinking in discussion on the cycle I: 73.07 %, cycles II: 81.25 %, cycles III: 87.5 %. The average value of students I: 77.31 cycle , cycle II: 80.38, cycleIII : 84.81. Minimal standards pass Â in cycles I: 69.23%, cycles II: 79.92% and cycles I: 88.4%.